Effect of Feeding Bypass Fat on Reproductive Performance in Surti Buffaloes - Patel, Parimal D.; Patel, Dilipkumar C.; Parmar, Ajaykumar P.; Parmar, Abhishek B.; Sarvaiya, Nitesh P.; Joshi, Prakash M. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
An experiment was conducted to evaluate the effect of feeding bypass fat on reproductive performance of Surti buffaloes. Fourteen  advanced pregnant Surti buffaloes were selected based on their records of daily milk yield and milk fat percent. The buffaloes were  divided into two groups: Control (T1) and Treatment group (T2) with seven animals in each group. The buffaloes in control group were  fed with green fodder, dry fodder and concentrate mixture as per ICAR requirements, while animals of treatment group received the  same ration but were supplemented with bypass fat @ 130 g/d prepartum for one month and 30 g/kg milk yield for three months  postpartum. The days required for uterine involution was significantly (p
Keywords: Bypass fat; Postpartum fertility; Surti buffaloes; Uterine involution